Utilization of Kahoot! As an English Learning Media - Eka Resty Novieta Sari (Peneliti.net, 2022)
The transition from conventional learning to online learning is not an easy thing, especially in English courses. Students consider that English courses are difficult subjects. Students assume that English is a difficult subject to understand. As a result, appropriate learning media are required, one of which is kahoot media. This study used a qualitative approach, with semester 1 students in the PGRI Madiun University's class B Informatics Engineering Study Program taking a direct quiz using the Kahoot program. Students were given a questionnaire relating to the use of kahoot media at the conclusion of the study, and the measuring scale utilized was the Likert scale with five indicators. The study's findings are as follows: 1) In the English learning process, kahoot media is employed as an easy-to-understand, entertaining, and creative learning medium. 2) Using Kahoot media can help students become more interested in learning. The use of kahoot media can assist students in being more interested in and motivated to learn English. Their English abilities can be strengthened as a result of this increase in interest and motivation. 3) The media kahoot quiz as an online learning innovation. The usage of kahoot aids lecture in giving creativity and innovation in learning material, as well as introducing pupils to the right use of technology.